(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Post-term pregnancy is a condition that raises many questions and concerns for expectant mothers and their families. The usual length of pregnancy is about 40 weeks, but sometimes the period can exceed this mark. This phenomenon brings with it not only physical but also emotional trials. A woman finds herself in a position where fear for the child’s health merges with the expectation of childbirth, and every movement, every change in well-being becomes a cause for concern. In this regard, post-term pregnancy is a complex, multifaceted process that requires careful approach and monitoring by medical specialists.